THE CRIMINAL ACT OF ILLEGAL MINING OF SAND AND GROSOK - Hadawiyah, Robiatul; Subekti; Soekorini, Noenik (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2023)
The control of minerals and coal by the state as referred to in Paragraph (1) is organized by the Government and Regional Governments. The purpose of this research is to understand and analyze the management of river sand mining and grosok in accordance with applicable laws and regulations in Indonesia, also examine and analyze criminal law enforcement on illegal mining of river sand and grosok. This research is included in normative legal research. The results showed that to conduct community mining activities in river sand mining according to Law No. 4/2009 concerning Mineral and Coal is Article. 1 number 10; Article. 1 number 12; Article. 20; Article. 21; Article. 22; Article. 24; Article. 25; Article. 26; Article. 35; Article. 67; Article. 68; Article. 69; Article. 70; Article. 72; Article. 73; Article. 104; Article. 131 and Article 132 with their criminal sanctions are contained in Article. 158, Article, 159 and Article. 165. The investigation of criminal act of illegal mining of river sand and grosok by police officers of the Directorate of Special Criminal Investigation of East Java Regional Police resulted in the conclusion that there was a criminal act of illegal mining by everyone who conduct the mining without a permit, as referred to in Article 158 of Law of Republic Indonesia No. 3/2020 concerning amendments to Law of Republic Indonesia No. 4/2009 concerning Mineral and Coal Mining, which has been amended by Law of Republic Indonesia No. 11/2020 concerning Job Creation.